Penguatan karakter Pemuda Desa Sambelia Malalui Gawa Adat “ Selametan Otak Reban” - Junaidi, Junaidi; Anwar, Faizi; Salwa, Nada; Zulfiana, Siti; Hadi, Mashal (PELITA NUSA TENGGARA, 2026)
The purpose of this community service activity is to strengthen the character of the young men and women of Sambelia village through the traditional gawe